The export of the DNA replication inhibitor Microcin B17 provides immunity for the host cell. - Garrido, M C (1988)
Microcin B17 (MccB17) is a peptide antibiotic which inhibits DNA replication in Enterobacteriaceae. Microcin-producing strains are immune to the action of the microcin. Physical and genetic studies showed that immunity is mediated by three genes: mcbE, mcbF and mcbG. We sequenced these genes and identified polypeptide products for mcbF and mcbG. By studying the contribution of each gene to the expression of immunity we found that immunity is determined by two different mechanisms. One of these, encoded by mcbE and mcbF, is also involved in the production of extracellular MccB17. To reconcile these observations we propose that McbE and McbF serve as a 'pump' for the export of active MccB17 from the cytoplasm. This model is supported by the predicted properties of the McbE and McbF proteins, which are thought to be, respectively, an integral membrane protein and an ATP-binding protein with homology to other transport proteins.